A Traumatic Experience in The Fallout Movie Directed by Megan Park - Insiyah (CV. Kalimasada Group Profesional, 2023)
Trauma is a condition that arises as a result of a scary experience or event, such as natural disasters, physical violence, sexual harassment, etc. The response caused by trauma is post-traumatic stress disorder, which affects a person's mentality due to the traumatic event he experienced. The purpose of this study is to know the causes and effects of post-traumatic disorders and the types of trauma in general. In this study, the writer used a descriptive-qualitative method. The writer watches the movie and identifies the data, then writes it back in the notebook and categorizes the data based on theory. In this study, the writer found that in the Fallout movie, the symptoms caused by trauma and post-traumatic experiences varied, such as intrusiveness, avoidance, and arousal. As well as the efforts made to get out of trauma, namely by coming to psychology, looking for activities, and being an open person with parents about anything. Hopefully this thesis can educate all of us about the dangers and impact of post-traumatic stress disorder, be useful, and contribute as an analysis of literary works, especially for English and English literature majors.